2020
DOI: 10.3390/app10217729
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Estimation of Roller Chain Power Transmission System

Abstract: In the present study, a novel approach to estimating the efficiency of roller chain power transmission systems is proposed based on sliding friction losses and damping force. The dynamics model is taken into account between chain links with lateral offset owing to the derailleur system. Frictional losses were calculated according to Coulomb’s law of friction, and the damping force was dependent on the damping coefficient. The effects of rotational speed, load, derailleur system, and damping coefficient on tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The sprocket system is an essential part of the rotary transmission in cycling. It has high reliability, flexibility, cost efficiency, and slip elimination (Ji et al, 2021;Lee et al, 2020;Zhai et al, 2019;Zhang and Tak, 2020). Several studies have sought to improve the sprocket system's mechanical efficiency, such as developing a new pedal-crank system (Hyeong et al, 2017;Ismail et al, 2020;Zamparo et al, 2002), investigating sprocket tooth profile to reduce chain friction and energy impact (Seller and Mezeix, 2019;Wang et al, 2013), investigating an optimized tooth model for chain shifting (Kim, 2013;Lai et al, 1998;Lin and Tseng, 1998;Ma and Chiou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The sprocket system is an essential part of the rotary transmission in cycling. It has high reliability, flexibility, cost efficiency, and slip elimination (Ji et al, 2021;Lee et al, 2020;Zhai et al, 2019;Zhang and Tak, 2020). Several studies have sought to improve the sprocket system's mechanical efficiency, such as developing a new pedal-crank system (Hyeong et al, 2017;Ismail et al, 2020;Zamparo et al, 2002), investigating sprocket tooth profile to reduce chain friction and energy impact (Seller and Mezeix, 2019;Wang et al, 2013), investigating an optimized tooth model for chain shifting (Kim, 2013;Lai et al, 1998;Lin and Tseng, 1998;Ma and Chiou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In [5], non-linear stiffness properties are exploited to dampen cable vibrations. Finally, in [8], non-linear effects are estimated to find chain transmission efficiency.…”
Section: Non-linear Analysismentioning
confidence: 99%
“…A novel approach for estimating the efficiency of roller chain power transmission systems is proposed in [8]. It is based on sliding friction losses and damping force.…”
Section: Machine Elementsmentioning
confidence: 99%
“…Although the method [6] using hardware-in-the-loop simulation for the electric bicycle driven on a motor dynamometer shows an energy efficiency error rate of 0.06% between the simulation and field test, it does not take into consideration the transmission system of the electric bicycles. When only the chain drive system estimation is considered [11], it is reported that the transmission efficiency error rate of the chain drive system itself is 0.23-3.77%; thus, the error rate is expected to increase significantly when other transmission components are considered. It can be concluded that the estimated transmission efficiency in this study can evaluate the performance of electric bicycles with reasonable accuracy considering all the components of transmission systems.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…However, there was no experimental validation to support the results. In Zhang et al [11], the transmission efficiency of the chain drive system was calculated considering the sliding friction force of pin articulation and bush articulation, lateral offset due to the derailleur system, and damping force between two sprockets. The transmission efficiency was computed considering the rotational speed of the sprocket, lateral offset angle, and torque.…”
Section: Introductionmentioning
confidence: 99%